CONTESTATION OF CHEMICAL CASTRATION PUNISHMENT FOR CHILD SEX OFFENDERS: CASE IN INDONESIA (UUM Journal of Legal Studies, 2022)
Children as national assets must receive significant concerns from their families, neighborhoods, and the state. Based on these circumstances, a variety of regulations are made, including the protection of children from sex offenders. Various arguments, both pro and contra, emerge in the regulation, which provides chemical castration punishment for child sex offenders. The objective of this article is to analyze the contesting of the chemical castration paradigm, both from theoretical and practical dimensions. It used a conceptual and legislative approach, through the analysis of several relevant books and articles as well as the opinions of qualified experts, which were then linked to one another. This paper argued that regardless of human rights perspectives, Indonesia’s future which lies in its future generations must receive more considerable attention. Therefore, the limitation of the perpetrators’ human rights should not be considered a human rights violation. Instead, this castration punishment protects the perpetrators’ human rights from a cruel retributive action from the victims’ family.